2022
DOI: 10.3389/fmolb.2022.901322
|View full text |Cite
|
Sign up to set email alerts
|

Corrigendum: Sevoflurane Alleviates Myocardial Ischemia Reperfusion Injury by Inhibiting P2X7-NLRP3 Mediated Pyroptosis

Abstract: There is an error in the Funding statement. The correct number for "the National Natural Science Foundation of China" is " 81473215 and 81870276".Additionally, in the original article, there was a mistake in "Figures 2-4" as published. The problem was caused by the incomplete uploading of some figures in the process of uploading revised manuscripts and figures before publication. We did not carefully check it, which led to the error when publishing the article. The correct figures appear below:Publisher's Note… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Several studies have demonstrated that sevoflurane has a protective effect on MIRI by suppressing the inflammatory response. A review by Wu et al indicated that the inhibition of cardiomyocyte inflammation and pyroptosis by regulation of the P2X7-NLRP3 signaling pathway is a potential mechanism of sevoflurane against MIRI [ 113 ]. Briefly, it was observed that sevoflurane treatment suppressed the high expressions of P2X7, NLRP3, ASC, caspase-1, and GSDMD and the release of LDH, CK, CK-MB, and MDA in the cells, and increased the activity of SOD.…”
Section: Inhibition Of Pyroptosis By Drugs and Improved Mirimentioning
confidence: 99%
“…Several studies have demonstrated that sevoflurane has a protective effect on MIRI by suppressing the inflammatory response. A review by Wu et al indicated that the inhibition of cardiomyocyte inflammation and pyroptosis by regulation of the P2X7-NLRP3 signaling pathway is a potential mechanism of sevoflurane against MIRI [ 113 ]. Briefly, it was observed that sevoflurane treatment suppressed the high expressions of P2X7, NLRP3, ASC, caspase-1, and GSDMD and the release of LDH, CK, CK-MB, and MDA in the cells, and increased the activity of SOD.…”
Section: Inhibition Of Pyroptosis By Drugs and Improved Mirimentioning
confidence: 99%